The Role of Direct Observed Treatment in Tuberculosis Treatment Successful at Community - Nursalam Nursalam; Makhfudli Makhfudli; Dominikus Rato (Universitas Airlangga, 2009)
Introduction : The succeeded of the tuberculosis treatment depends on the obedience of the patient in taking the tuberculosis’s medication assisted by the direct observed treatment shortcourse (DOTS) to refrain resistancy and dropping out of the program. The aimed of this study was to analyze the correlation between DOTS’s role with the successfullness of lung’s tuberculosis treatment program at Bajawa city.Methods : A cross sectional simple random sampling design was used in this study. Population were all the Direct Observed Treatment Supervisors and patients who have had finished their treatment of tuberculosis. Sample were 43 respondents. The independent variables in this study were the role of the DOTSs, education level, family support, motivation and the DOTSs attitude. The dependent variables were the patient’s obedience in taking medication and the evaluation of the acid fast bacterias in their sputum. Data were collected by using questionnaire and observation sputum the to evaluate acid fast bacteria. Data were analyzed by using Spearman Rho with significance level with α<0.05.Results : The result showed that role of the DOTSs had significance correlation with the succeeding program of tuberculosis (r=0.023), education level had significance correlation (r=0.043), family support as the DOTS had significance correlation (r=0.021), motivation (r=0.032) and attitude (r=0.014).Conclusion: It can be concluded that the role of the DOTS has correlation with succesing tuberculosis treatment. Discussion : The role of PMO cause the succesfully of Tb treatment for the community in Bajawa City, Ngada NTT.